Plasma stromal cell-derived factor 1α/CXCL12 level predicts long-term adverse cardiovascular outcomes in patients with coronary artery disease. Issue 1 (January 2015) - Ghasemzadeh, Nima; Hritani, Abdul Wahab; De Staercke, Christine; Eapen, Danny J.; Veledar, Emir; Al Kassem, Hatem; Khayata, Mohamed; Zafari, A.Maziar; Sperling, Laurence; Hooper, Craig; Vaccarino, Viola; Mavromatis, Kreton; et al.
Abstract Objective: Stromal derived factor-1α/CXCL12 is a chemoattractant responsible for homing of progenitor cells to ischemic tissues. We aimed to investigate the association of plasma CXCL12 with long-term cardiovascular outcomes in patients with coronary artery disease (CAD). Methods: 785 patients aged: 63 ± 12 undergoing coronary angiography were independently enrolled into discovery (N = 186) and replication (N = 599) cohorts. Baseline levels of plasma CXCL12 were measured using Quantikine CXCL12 ELISA assay (R&D systems). Patients were followed for cardiovascular death and/or myocardial infarction (MI) for a mean of 2.6 yrs. Cox proportional hazard was used to determine independent predictors of cardiovascular death/MI. Results: The incidence of cardiovascular death/MI was 13% (N = 99). High CXCL12 level based on best discriminatory threshold derived from the ROC analysis predicted risk of cardiovascular death/MI (HR = 4.81, p = 1 × 10−6) independent of traditional risk factors in the pooled cohort. Addition of CXCL12 to a baseline model was associated with a significant improvement in c-statistic (AUC: 0.67–0.73, p = 0.03). Addition of CXCL12 was associated with correct risk reclassification of 40% of events and 10.5% of non-events. Similarly for the outcome of cardiovascular death, the addition of the CXCL12 to the baseline model was associated with correct reclassification of 20.7% of events and 9% of non-events. These results were replicated in two independent cohorts. Conclusion: Plasma CXCL12 level is a strong independent predictor of adverse cardiovascular outcomes in patients with CAD and improves risk reclassification.